Association genetics, geography and ecophysiology link stomatal patterning in Populus trichocarpa with carbon gain and disease resistance trade‐offs. Issue 23 (8th November 2014) - McKown, Athena D.; Guy, Robert D.; Quamme, Linda; Klápště, Jaroslav; La Mantia, Jonathan; Constabel, C. P.; El‐Kassaby, Yousry A.; Hamelin, Richard C.; Zifkin, Michael; Azam, M. S.
Abstract Stomata are essential for diffusive entry of gases to support photosynthesis, but may also expose internal leaf tissues to pathogens. To uncover trade‐offs in range‐wide adaptation relating to stomata, we investigated the underlying genetics of stomatal traits and linked variability in these traits with geoclimate, ecophysiology, condensed foliar tannins and pathogen susceptibility in black cottonwood (Populus trichocarpa). Upper (adaxial) and lower (abaxial) leaf stomatal traits were measured from 454 accessions collected throughout much of the species range. We calculated broad‐sense heritability (H2) of stomatal traits and, using SNP data from a 34K Populus SNP array, performed a genome‐wide association studies (GWAS) to uncover genes underlying stomatal trait variation. H2 values for stomatal traits were moderate (average H2 = 0.33). GWAS identified genes associated primarily with adaxial stomata, including polarity genes (PHABULOSA), stomatal development genes (BRASSINOSTEROID‐INSENSITIVE 2) and disease/wound‐response genes (GLUTAMATE‐CYSTEINE LIGASE). Stomatal traits correlated with latitude, gas exchange, condensed tannins and leaf rust (Melampsora) infection. Latitudinal trends of greater adaxial stomata numbers and guard cell pore size corresponded with higher stomatal conductance (gs) and photosynthesis (Amax), faster shoot elongation, lower foliar tannins and greater Melampsora susceptibility. This suggests an evolutionary trade‐off related to differing selection pressures across the species range. In northern environments, more adaxial stomata and larger pore sizes reflect selection for rapid carbon gain and growth. By contrast, southern genotypes have fewer adaxial stomata, smaller pore sizes and higher levels of condensed tannins, possibly linked to greater pressure from natural leaf pathogens, which are less significant in northern ecosystems.